Human-Centric Information Processing Through Granular Modelling - Bargiela, Andrzej; Pedrycz, Witold (Studies in Computational Intelligence, 2009)
The idea of Human-Centric Information Processing was prompted by the pioneering work of Zadeh Towards a theory of fuzzy information granulation and its centrality in human reasoning and fuzzy logic (1997). Since the publication of this work, a large number of researchers have focused on identifying the nature of information granulation and its specific relationship to human information processing. We now begin to witness the rich and manifold results of this concentrated research effort of the last decade. This volume is intended to document the milestone contributions to human-centric information processing research and to demonstrate the emerging computational methods and the processing environments that arose from these research insights. The chapters, written by experts in the field, cover the fundamental methodologies, the new information processing paradigm, functional architectures of granular information processing and granular modeling applications. The book provides a valuable reference for researchers, graduate students intending to focus on particular aspects of human-centric information processing from a broadly informed perspective and for practitioners to whom the breadth of coverage of topics will help inspire innovative applications.